2002
DOI: 10.1091/mbc.02-02-0022
|View full text |Cite
|
Sign up to set email alerts
|

Pink-eyed Dilution Protein Controls the Processing of Tyrosinase

Abstract: The processing of tyrosinase, which catalyzes the limiting reaction in melanin synthesis, was investigated in melan-p1 melanocytes, which are null at the p locus. Endoglycosidase H digestion showed that a significant fraction of tyrosinase was retained in the endoplasmic reticulum. This retention could be rescued either by transfection of melan-p1 cells with an epitope-tagged wild-type p transcript or by treatment with either bafilomycin A1 or ammonium chloride. We found that the endoplasmic reticulum contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 43 publications
4
76
0
Order By: Relevance
“…Though pre-melanosomes and melanosomes possess highly-acidic contents (Moellmann, et al , 1988, Ancans, et al , 2001, Chen, et al , 2002, Schallreuter, et al , 2008), their contents approach neutrality immediately prior to secretion (Ancans, et al , 2001), an antecedent that is apparently necessary for pigment transfer (Seiberg, 2001, Boissy, 2003). Melanin granules then are secreted into the extracellular spaces before being phagocytized by neighboring keratinocytes (Ando, et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though pre-melanosomes and melanosomes possess highly-acidic contents (Moellmann, et al , 1988, Ancans, et al , 2001, Chen, et al , 2002, Schallreuter, et al , 2008), their contents approach neutrality immediately prior to secretion (Ancans, et al , 2001), an antecedent that is apparently necessary for pigment transfer (Seiberg, 2001, Boissy, 2003). Melanin granules then are secreted into the extracellular spaces before being phagocytized by neighboring keratinocytes (Ando, et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Melanocytes could regulate epidermal function (including acidification) by paracrine influences (Slominski and Paus, 1990, Slominski, et al ., 1993), and/or by `juxtacrine' effects of melanocytes on neighboring keratinocytes. Melanosomes are acidic organelles that enclose several proteins in the eumelanin synthetic pathway (Moellmann, et al ., 1988, Schallreuter, et al ., 2008), whose activities require a reduced pH (Chen, et al ., 2002). Although the internal pH of melanosomes increases immediately prior to secretion (Ancans, et al ., 2001), our studies showed that putative melanosomes in dendrites of darkly-pigmented human melanocytes are more acidic than comparable vesicular structures in lightly-pigmented subjects (Gunathilake, et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The P gene encodes an integral melanosomal membrane protein composed of 833 amino acids with 12 putative transmembrane domains [23,24]. The function of the P gene product has not yet been clarified, although several potential functions have been proposed, including, membrane transport [25], sorting of tyrosinase to melanosomes [26], stabilization of a melanosomal protein complex [27], regulation of melanosomal pH [28], and control of tyrosinase processing, arsenic sensitivity and cellular glutathione metabolism [29][30][31].…”
Section: 1 Major Features Of Oca2mentioning
confidence: 99%
“…[22], although, that interpretation was later questioned [23]. A later study suggested that the P protein localizes to and functions in the endoplasmic reticulum (ER) [24] but it was recently reported that the human P protein is rapidly processed by Golgi enzymes [25] and transits to lysosome-related organelles (LROs) via BLOC-1, a complex protein involved in protein trafficking [26,27].…”
Section: Introductionmentioning
confidence: 99%